Optimalisasi Potensi Lokal Melalui Kuliah Kerja Nyata (KKN) di Dusun Sundan, Desa Plaosan, Kabupaten Malang - Purborini, Vivi Sylvia; Masela, Minggus S.; Zidny, Hilman; Sastraningsih, Anak Agung Putri; Sholihah, Lik Bawon; Anjanni, Arimbi Rayi (Abdimas Indonesian Journal, 2025)
Real Work Lectures (KKN) is a form of community service carried out by students as part of the Tri Dharma of Higher Education. Through KKN, students are expected to be able to apply the knowledge they have gained during their studies to help solve problems that exist in society. The method used when implementing Real Work Lectures (KKN) consists of several main stages, namely briefing from campus, location survey, village mapping, and member coordination. Each stage is carried out systematically to ensure activities run effectively and in accordance with community needs. Apart from benefits for students, the KKN program also has a positive impact on the local community. Several work programs that have been implemented, such as psychoeducation, teaching assistance in elementary and kindergarten, planting coffee seedlings and helping to renovate several existing facilities in the village can be handled through good cooperation between students, supervisors and the community.